AHŞAP KOLONLARININ TABİİ YANGIN DİZAYNI - SAVAŞ, SEDAT (Fırat Üniveristesi, 1995)
Ahşap çok eski zamanlardan buyana kullanılan bir yapı dananı olmuştur. Özellikle savaş yıllarında diğer yapı malzemelerinin temininin zorluğundan dolayı kullanımı çoğalmıştır. Ancak diğer yapı malzemeleri gibi ahşapta yangından büyük ölçüde etkilendiğinden zamanla çeşitli standartlar yaymlanmıştır.(DIN 4102 Kısmı 2 ve Kısım 4). Daha önce yapılan çalışmalarla norm yangım etkisi amadaki ahşap kolonların yangına dayanım süreleri bulunmuştur. Fakat gerek deneysel gerekse teorik olarak ISO 834yangınma göre sıcaklıklar sürekli artış gösterdiğinden gerçek bir yangın ortamı ile birleşmemektedir. Çünkü tabii yangınlarda ısınma ve parlama (flash over) fazı sonunda soğuma fazı gelmektedir. Bu nedenle ahşap kolonların bazı tabii yangın etkilerine karşı göçme gösteremiyeceği bilinmektedir. Ayrıca mevcut yangın yükleri gözönüne alındığında termik etki bir ISO 834 yangınından daim düşük olacağı için ahşap kolon dizaynında daha küçük kesitler bulunabilir. Bu sebeplerden dolayı, yaptığımız çalışmada tabii yangına göre ahşap kolon dizaynı yapılmıştır. Yapılan deneysel ve teorik ön çalışmalar sonucu, eşdeğer yangın süresine bağlı olarak ahşap kesitlerde kömürleşme hızı saptanmıştır. Ayrıca numunelerin elastisite modülü ve basınç dayanımı deneysel olarak bulunmuştur. Bu ön çalışmaların sonucunda tabii yangın etkisi altındaki ahşap kolonların servis yükü atanda yangına dayanım süresini, kömürleşme hızını, elastik modülünü ve bu değerlere göre seçilecek kesit abakları verilmiştir. Sonuçlar tabii ahşap kesitler için bulunmuş olup, lamelli-ahşap kesitler için geçerli ANAHTAR KELİMELER: Yangın Dzaynı Ahşap Kolon, Kömürleşme Oranı, İkinci Mertebe Teorisi, Tabii Yangın, Yük Taşıma Kapasitesi Yangın Korunumu.

w SUMMARY Master Thesis FIRE ENGINEERING DESING OF WOOD COLUMNS IN CASE OF REAL FIRES Sedat SAVAŞ Fırat University Graduate School of Natural and Applied Sciences Department of Civil Engineering 1995,Page:72 In the last few decades, great advances have been made in the field of analytical fire design of loadbearing structures. The aim is to devise a design procedure which is based on the properties of the real fire proces and well-defined functional requirements and performance criteria For a loadbearing structure whose constructional data are specified, the design fire exposure, together with data concerning the thermal properties of the material contained in the load bearing element, provides the basis required for determination of the fire resistance of the structures. When the mechanical properties of the load beaming wood material at elevated temperatures are known, these temperature fields can be converted by calculation in to stress state and load deflection behaviour at varying temperature and load levels of the loadbearaing structure. Realeted to a failure criterions the verification in time of the loadbeaming capacity of the structure can then be calculated. For timber structure expased to fire we also need an analytical model for calculation of the rate of charring of the cross section under variable termal exposure. The main objective of this study is to develop an analytical model for dcterminationA,f the tempareture state, charring of wood as well as defermation state of timber structures exposed to fire. In this study, the ideas of previous works have been further devloped and improved. This is particulary true in regard to the model for charring rate in case of real fire exposure. This study also includes well defined experiments as an essential ingredient In these experiments, fundamental variables such as the hot gas temperature, temperature development in cross-section rate of charring and equivalent fire duration have been recorded. This relatively complate experimental setup enables verifaction of the analytical model to be carried out By this, discussion of the developed model in conzuction with comparison of the numerical results with the measured relationships are made, which resulted in finary preparation of the design charts of wood columns under real fire action. A good agreement is observed between the experimental and the calculated results. KEYWORDS: Fire enginering, desing. Fire Safely, Fire Protection, Wood Columns, Charring Rate, Second Order Theory, Real Fire, Loadbearing Capacity, Pyroiysis, Wood.
Fire engineering desing of wood columns in case real fires
Keywords: İnşaat Mühendisliği; Civil Engineering